When Labor Disputes Bring Cities to a Standstill: The Impact of Public Transit Strikes on Traffic, Accidents, Air Pollution, and Health - Timo Hener; Helmut Rainer; Stefan Bauernschuster (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
There is widespread concern that major cities and their inhabitants are highly vulnerable to transit strikes. Governments in many countries have addressed this concern by limiting the right of transit workers to strike. Whether or not this can be justified depends, in turn, on whether strikes by transit workers implicate the safety or health of urban populations and impose disproportionate costs on non-involved third parties. We use time series and cross-sectional variation in powerful registry data in order to quantify the effects of public transit strikes in five population-relevant domains: traffic volumes, travel times, accident risk, pollution emissions, and health. The context of our study are the five largest cities in Germany, allowing us to exploit 71 public transit strikes over the period from 2002 to 2011. Generalized difference-in-differences models suggest that strikes lead to a significant increase in car traffic, congestion, accident risk and air pollution. There is also evidence for a substantial increase in accident-related injuries and pollution-related health problems. The third party congestion costs of public transit strikes exceed the private costs of struck employers by at least a factor of four.
Keywords: J00; J58; K31; 330